Why do apprentices smoke much more than high school students? Understanding educational disparities in smoking with a Oaxaca-blinder decomposition analysis - Sandra Chyderiotis; Tarik Benmarhnia; Stanislas Spilka; François Beck; Raphaël Andler; Stéphane Legleye; Gwenn Menvielle (BMC, 2020)
Abstract Background Educational disparities in daily smoking begin during adolescence and can lead to educational disparities in health among adults. In particular, vocational students including apprentices have higher daily smoking rates compared to non-vocational students. This study aimed to identify the determinants of the gap in daily smoking between French apprentices and high school students aged 17 in 2008 and in 2017. Methods We used data from a cross-sectional repeated survey representative of all French adolescents aged 17 in 2008 and 2017. We conducted a non-linear extension of the Oaxaca-Blinder decomposition technique and included the following variables: sociodemographic and familial characteristics, parental smoking, cannabis and alcohol use, suicidal attempt, grade repetition and money received. Results Daily smoking was about two times higher among French apprentices compared to high school students in 2008. This gap did not decrease between 2008 and 2017. Differences in measured characteristics between the two groups explained this gap partly, from 28.6 to 51.2%. Cannabis and alcohol use, money received and parental smoking contributed the most to the daily smoking gap. Conclusions Prevention programs could target cannabis and alcohol use as well as parental smoking to help decrease educational disparities in smoking status among French adolescents.